2021
DOI: 10.1515/mt-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Wear behavior and microstructure of Fe-C-Si-Cr-B-Ni hardfacing alloys

Abstract: This study aims to investigate the relationship between wear resistance and microstructure of a hardfacing alloy Fe-C-Si-Cr-B-Ni system as well as investigating ways of improving the hardness of the hard facing layer through the addition of nickel to achieve a finer granular microstructure. Three hardfacing alloys are used for overlaying. Ferroboron (FeB) and Ferronickel(FeNi), are added to the massive wire during the welding process. A hardness test, microscopic characterization and wear analysis are carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It was found that the wear resistance of hardfacing depends on the microstructure obtained after hardfacing and the parameters of the depositing process. Öztürk [31] studied the wear behaviour and microstructure of Fe-C-Si-Cr-B-Ni hardfacing alloys, with the addition of ferronickel (FeNi) and ferroboron (FeB). It was found that, at room temperature, wear occurs through a combination of local delamination of surface layer and abrasive grooving.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the wear resistance of hardfacing depends on the microstructure obtained after hardfacing and the parameters of the depositing process. Öztürk [31] studied the wear behaviour and microstructure of Fe-C-Si-Cr-B-Ni hardfacing alloys, with the addition of ferronickel (FeNi) and ferroboron (FeB). It was found that, at room temperature, wear occurs through a combination of local delamination of surface layer and abrasive grooving.…”
Section: Introductionmentioning
confidence: 99%
“…Fe-C-B-Cr alloys has excellent wear resistance, good corrosion resistance, and oxidation resistance [8]. The more widespread by Fe-Cr-B-C and Fe-Cr-B-C-Ti system alloys, which have the best mechanical properties and wear resistance [10][11][12][13]. Available information suggests that the abrasive wear resistance of materials depends on factors like microstructure (their size and content), and mechanical properties of materials [14].…”
Section: Introductionmentioning
confidence: 99%